Предмет: Математика,
автор: Crave1
Решите уравнение
Ответы
Автор ответа:
0
сos^2(pi*x/6)>=0
√(2*x^2-5x-3)>=0
Откуда 0 ,будет лишь когда обе функции равны 0.
2*x^2-5x-3=0
D=25+24=49
x=(5+-7)/4
x1=3
x2=-1/2
НО только при x=3
оно обращает cos^2(pi*x/6)=cos^2(pi/2)=0
при x=-1/2 не обращает.
Ответ:x=3
√(2*x^2-5x-3)>=0
Откуда 0 ,будет лишь когда обе функции равны 0.
2*x^2-5x-3=0
D=25+24=49
x=(5+-7)/4
x1=3
x2=-1/2
НО только при x=3
оно обращает cos^2(pi*x/6)=cos^2(pi/2)=0
при x=-1/2 не обращает.
Ответ:x=3
Похожие вопросы
Предмет: История,
автор: Аноним
Предмет: ОБЖ,
автор: help7386
Предмет: Литература,
автор: kylizadefatma
Предмет: Математика,
автор: юмуш2003
Предмет: Биология,
автор: da259